Peranan Badan Pengawas Pemilu dalam Penyelesaian Sengketa Pada Pemilihan Legislatif Tahun 2019 Di Kota Medan - Daeli, Sri Suci Mentari; Batubara, Beby Masitho; Jamil, Bahrum (Strukturasi: Jurnal Ilmiah Magister Administrasi Publik, 2021)
The dispute in the 2019 legislative election in Medan is a process dispute that occurs between election participants or legislative candidates against the election organizer or KPU. In the registration of participants, the KPU legislative candidates rejected the PKB National Awakening Party due to delays in registering legislative candidates. Related to the decision issued by the participating KPU filed a request dispute to the Medan city Bawaslu to follow up on the decision. In filing a petition dispute, there are several things that must be fulfilled, including: completing the identity of both the applicant and the respondent. The purpose of this research is to find out the dispute that accurred between PKB and KPU which was held by the Medan city Bawaslu in resolving disputes in the 2019 legislative elections in Medan. This study uses qualitative methods as data analysis. The source of data in this research is the head of the Medan city Bawaslu and the dispute settlement division. Data were collected based on data collection techniques, namely literature, observation, interviews, documentation and data triangulation. Bawaslu’s role is to carr out mediation and adjudication hearings by inviting both parties as applicants and defendants to resolve the dispute. After the mediation, the adjudication trial is held, the Bawaslu has the right to inspect, study and decide for twelve (12) working days. The decision announced by the Bawaslu was to reject PKB election participants as legislative candidates and the statement was the final decision.